-10-3h=8h+3+9

Simple and best practice solution for -10-3h=8h+3+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10-3h=8h+3+9 equation:


Simplifying
-10 + -3h = 8h + 3 + 9

Reorder the terms:
-10 + -3h = 3 + 9 + 8h

Combine like terms: 3 + 9 = 12
-10 + -3h = 12 + 8h

Solving
-10 + -3h = 12 + 8h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-8h' to each side of the equation.
-10 + -3h + -8h = 12 + 8h + -8h

Combine like terms: -3h + -8h = -11h
-10 + -11h = 12 + 8h + -8h

Combine like terms: 8h + -8h = 0
-10 + -11h = 12 + 0
-10 + -11h = 12

Add '10' to each side of the equation.
-10 + 10 + -11h = 12 + 10

Combine like terms: -10 + 10 = 0
0 + -11h = 12 + 10
-11h = 12 + 10

Combine like terms: 12 + 10 = 22
-11h = 22

Divide each side by '-11'.
h = -2

Simplifying
h = -2

See similar equations:

| (4m-120)= | | -8(r-6)=-8-6(-2+5r) | | -13m+7m=18-66 | | 8.7x=156.6 | | 5x-(3x-2)=18 | | -8x-8=3x+25 | | -8-5(1+6x)=5(1-6x)2x | | -3+a/4=-4 | | V+4-8=6(v+7)+2(v+5) | | 8(x-7)=-112 | | -12-11d=-10d | | ax+bx=-4 | | X=10x-78 | | 3x+4x=6x-8 | | 2x+5+2x-23=90 | | -5+b/8=-4 | | -7(x+3)=3(-5-2x) | | 19=-3+4(v-6) | | 2(x+3)-3x-7=2 | | x+x+x+16=25 | | 7t+6=8t | | x^2+y^2-2xy=144 | | 2a+4b+a-b+10= | | (3xy^3)-3xy=0 | | z(z-i)=iz+2 | | 7x+12=40+3x | | t/9--118=130 | | -7a+1=8(1-a)+1 | | -7b-7=-b-7 | | (2a-6)(3a-15)=0 | | -2(v-882)=162 | | z(z-i)=je+2 |

Equations solver categories